2021
DOI: 10.1097/dss.0000000000003152
|View full text |Cite
|
Sign up to set email alerts
|

Robotically Assisted Recipient Site Preparation in Hair Restoration Surgery: Surgical Safety and Clinical Outcomes in 31 Consecutive Patients

Abstract: BACKGROUND Recent advances in robotic surgery have extended to hair restoration surgery, using a robotic recipient site creation device. OBJECTIVE This study aimed to assess the surgical safety and postoperative clinical outcomes of using this robotic system. MATERIALS AND METHODS Thirty-one men diagnosed with androgenetic alopecia, who underwent hair transplantation with robotic recipient site creation, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…33 Kanayama et al evaluated the performance of a robotic recipient site creation device in 31 patients and found the robotic tool to be safe and reliable for clinical use, as well as easily manageable by different HT surgeons. 34 A 2015 Korean study reported similar outcomes in 22 HT patients. The authors outlined the benefits of such devices in overcoming the increasing human error rate when performing repetitive tasks.…”
Section: Discussionmentioning
confidence: 91%
“…33 Kanayama et al evaluated the performance of a robotic recipient site creation device in 31 patients and found the robotic tool to be safe and reliable for clinical use, as well as easily manageable by different HT surgeons. 34 A 2015 Korean study reported similar outcomes in 22 HT patients. The authors outlined the benefits of such devices in overcoming the increasing human error rate when performing repetitive tasks.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, it can easily be controlled by a diverse range of hair surgeons. [ 18 ] Cluster 5 emphasized skin disease classification via image analysis. Several studies have analyzed clinical and dermatopathological images to categorize skin lesions associated with various skin conditions such as basal cell carcinoma, melanoma, atopic dermatitis, onychomycosis, and rosacea.…”
Section: Discussionmentioning
confidence: 99%
“…[16] An automated robotic hair restoration device was introduced for clinical application in 2011, and its use has gained momentum worldwide as an alternative to manual follicular unit extraction. [17][18][19] Additionally, AI systems can provide outcome predictions and prognostic assessments for dermatological diseases. [20,21] Yeong et al [22] developed an artificial neural network-based algorithm to predict when a burn would heal, with an overall prediction accuracy of 86%.…”
Section: Introductionmentioning
confidence: 99%
“…It is safe to use on men with dark, straight hair, according to the FDA. With the use of an artificial intelligence algorithm and a high-definition stereoscopic vision system, the system can recognize and choose the ideal hair follicles for transplantation [15]. Fig.…”
Section: Artas Roboticmentioning
confidence: 99%